2015
DOI: 10.1016/j.ress.2015.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in leveraging existing human performance data for quantifying the IDHEAS HRA method

Abstract: This article documents an exploratory study for collecting and using human performance data to inform human error probability (HEP) estimates for a new human reliability analysis (HRA) method, the IntegrateD Human Event Analysis System (IDHEAS). The method was based on cognitive models and mechanisms underlying human behaviour and employs a framework of 14 crew failure modes (CFMs) to represent human failures typical for human performance in nuclear power plant (NPP) internal, at-power events [1]. A decisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Further, surveys and interviews rarely provide measures of performance that can be directly integrated into existing models. Instead, participants usually provide ordinal rankings or qualitative descriptions of their performance which must be converted manually into a quantitative format [19]. Little exact guidance exists on this practice, making researcher experience in the practice critical [20].…”
Section: Traditional Approaches To Quantify Human Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Further, surveys and interviews rarely provide measures of performance that can be directly integrated into existing models. Instead, participants usually provide ordinal rankings or qualitative descriptions of their performance which must be converted manually into a quantitative format [19]. Little exact guidance exists on this practice, making researcher experience in the practice critical [20].…”
Section: Traditional Approaches To Quantify Human Performancementioning
confidence: 99%
“…Further, these studies can be controlled such that the observed performance is minimally influenced by confounding factors. The drawback is that these studies can be time consuming and expensive to perform properly [19]. Designers report many difficulties engaging with end-user populations.…”
Section: Traditional Approaches To Quantify Human Performancementioning
confidence: 99%
“…As it stands, different studies have to be performed based on the different methods to test the different error rates, for the different subcomponents the different methods include. Also Liao et al [6] discuss the 011013-4 / Vol. 6, MARCH 2020…”
Section: Challenges With the Definitions Of Complexity And Complexitymentioning
confidence: 99%
“…A particular challenge in analyzing complexity in event reports is that the event reports are usually not very detailed and it is very difficult to understand which subcomponents of complexity are involved. Boring et al [3] and Liao et al [6] also say that the events occur so infrequently that they do not give much data for HRA. Also, another challenge in using event reports to collect HRA data for complexity is that when large accidents happen, such as, for example, the three mile island incident, ATHEANA [10] claims that these accidents are particularly complex.…”
Section: Difficulties In Obtaining Empirical Data On Complexity From mentioning
confidence: 99%
See 1 more Smart Citation